Modeling of damage in elastic plastic bodies - Burago, Nikolay Georgievich (Computational Continuum Mechanics, 2008)
Numerical aspects of continuum damage modeling are overviewed. The theoretical model, method and results of damage tension test modeling for elastic plastic specimens with macro-pores and rigid inclusions are presented. The macro-pores are directly modeled as circular and elliptic holes of various orientation. The equations of elastic-plastic flow theory are extended to include the kinetic equation for a scalar damage, and the dependence of elastic coefficients and yield limit on the damage is taken into account. It is assumed that the damage starts to grow if the maximal principal strain exceeds the limit value. As the damage grows, the values of elastic coefficients and yield limit tend to zero. It simulates the progressive degradation of elastic properties of the damaged material. The influence of macro-pores and rigid inclusions on spatially averaged stress-strain diagrams is investigated. On the basis of numerical experiments, the recommendations regarding the desirable properties of numerical methods for damage simulation are worked out.